Taguchi-based optimization of activation parameters in activated carbon production for water pollutant adsorption - I Gusti Agung Kade Suriadi; Dewa Ngakan Ketut Putra Negara; Tjokorda Gde Tirta Nindia; I Ketut Adi Atmika; I Gusti Komang Dwijana; I Made Gatot Karohika; Anak Agung Istri Agung Sri Komaladewi; Gopi Prasetiyo (Universitas Mercu Buana, 2026)
Water pollution from synthetic dyes, particularly methylene blue (MB), is known to pose serious environmental and public health challenges. Therefore, among various treatment methods, adsorption using activated carbon remained the most cost-effective and energy-efficient. In this research, activated carbon was prepared from Petung bamboo (Dendrocalamus asper), with the Taguchi method used to optimize the activation parameters. The following three factors: activation temperature (700°C, 800°C), holding time (40 min, 80 min), and activating gas (N₂, CO₂) were investigated based on an L4(23) orthogonal array design. The characterization process included proximate analysis, functional group identification, amorphous structure determination, and surface morphology examination. Optimization using the larger-is-better signal-to-noise (SN) ratio model aimed to maximize methylene blue adsorption. Additionally, analysis of variance (ANOVA) showed that activating gas, holding time, and temperature contributed 48.69%, 34.86%, and 8.06%, respectively, to adsorption performance, and all three parameters had a statistically significant influence on methylene blue adsorption. The optimal conditions, namely 800°C activation temperature, 40 min holding time, and N₂ gas, produced a maximum adsorption capacity of 9.275 mg/g. As a result, these findings showed that activated carbon derived from Petung bamboo was a sustainable and renewable adsorbent, offering a promising pathway toward environmentally friendly and cost-effective wastewater treatment technologies.